Prevalence and predictors of poor sleep quality among secondary school students in Gombak District, Selangor - Kesintha, Appanna; Gyanchand Rampal, Lekhraj Rampal; Mohd Sidik, Sherina; Thevandran, Kalaiselvam (Malaysian Medical Association, 2018)
Introduction: Poor sleep quality among adolescents is becoming a major worldwide concern and is widely recognized as a significant public health issue. Objectives: To determine the prevalence and predictors of poor sleep quality among secondary school students in Gombak District, Selangor. Methods: A cross-sectional study was conducted in Gombak District. The sample size was 1,092 based on two group comparison formula. Students were selected using sampling with probability to proportionate to size. Self administered pretested questionnaires were used to collect the data. The data were analysed using the Statistical Package for Social Sciences (SPSS) version 22. Chi-square or Fisher's exact test was performed to determine the association between individual categorical variables and sleep quality. Variables with p-value <0.25 were selected to be subjected into multivariate logistic regression to determine the predictors. Results: The response rate was 93.0%. The prevalence of poor sleep quality was 24.0% (95% CI = 21.5, 26.6). Based on the analysis of simple logistic regression seven variables that were significantly associated with poor sleep quality were age, gender, marital status of parents, depression, anxiety, stress and academic performance found fit in the model. Multivariate logistic analysis showed that the significant predictors of poor sleep quality were age, marital status of parents, depression, anxiety, stress and academic performance. Factors that were not statistically significant were gender, religion, ethnicity, parent's educational level and family income. Conclusions: Prevalence of poor sleep quality among adolescents is high. The predictors of poor sleep quality are age, marital status of parents, depression, anxiety, stress and academic performance.